An Analytical Research on Hydrogen Fuel Cell Technology - Srikiran Chinta, Hari Prasad Bhupathi, Dr Vijayalaxmi Biradar, Dr Sanjay Kumar Suman, (Journal of Computational Analysis and Applications (JoCAAA), 2025)
This paper investigates fuel cell technology, an efficient and environmentally friendly method forgenerating electricity by harnessing the energy content of hydrogen or alternative fuels. Fuel cells produceelectricity with water, heat, and power as the only by-products when hydrogen is used as fuel, making them a